Assessment of the Prevalence of the Co-infection among Human T Lymphotropic Virus Type 1 – Positive Individuals in Gabon: A Comparative Study of Loa loa and Mansonnella perstans - Jean-Paul Akue; Berthold Bivigou-Mboumba; Cindy M. Padilla; Mirdad Kazanji; Dieudonné Nkoghe (Disease and Health: Research Developments Vol. 5, 2025)
Background: Co-infection between pathogens is common in tropical areas. Therefore, the Interaction between pathogens that may affect the clinical outcome in this infected patient was hypothesized. Objective: This study aimed to assess the prevalence and coinfection patterns of HTLV-1 and filarial infections in Gabon. Methods: A survey was conducted throughout Gabon to search simultaneously for Human T-Lymphotropic Virus type 1 (HTLV-1) using quantitative polymerase chain reaction (qPCR) and the serological method as well as filarial infection on the same sample by direct examination of 10 µL of blood and the concentration technique. Results: In this study, 3728 samples were analyzed, showing that 8.3% (320/3728) were positive for HTLV-1, 22.3% (831/3728) exhibited Loa loa and 9.8% (366/3728) were positive for Mansonella perstans. A total of 95 (2.5%) individuals had HTLV-1–L. Loa coinfection and 33 (0.9%) HTLV1–M. perstans coinfection. Interestingly, there were more carriers of L. loa microfilaria positive for HTLV-1 than L. loa-negative individuals (10.1% vs. 6.7%, respectively; p=0.0004). Regarding Mansonella perstans distribution (another filarial species prevalent in Gabon), there was no significant difference between HTLV-1 / M. perstans carriers and non-carriers (7.4% vs. 7.9%, respectively; p=0.77). Furthermore, a density of Loa loa microfilariae over 30,000 microfilariae per milliliter influences HTLV-1 carriage (p=0.02). The prevalence of L. loa, M. perstans microfilaremia and HTLV-1 mono-infections and coinfections were higher in forest ecosystems than in savannah and Lakeland (p<0.001). Correlations were also found with age and sex. Conclusion: These results suggest that L. loa and not M. perstans microfilariae carriage may affect the carriage of HTLV-1. A relationship between sex, age, and the forest ecosystem is suggested. We hypothesize on the clinical implications of the study.